Pelajaran dan pengaruh kebudajaan Makassar-Bugis di pantai utara Australia - Cense, Anton Abraham (Seri terdjemahan karangan-karangan Belanda ;, 1972)
Makassarese and Buginese sea voyages to the northern coast of Australia and their cultural influence in the area; two essays.